Rhinosporidiosis: Report of an extra-ductal facial lesion. (2017) - Nambiar, Sapna S.; Radhakrishnan, Suma; Vijayan, Anusha
Abstract: Rhinosporidiosis is a chronic granulomatous mucocutaneous disease that is endemic in South Asia. It commonly affects men in the second to fourth decade of life. The most common site of infection is the nose or nasopharynx with primary involvement of the parotid duct noted very rarely; only four cases reported in literature. We report a case of a 77 year old male patient who presented with a subcutaneous cheek swelling with no other clinical features to suggest the diagnosis of rhinosporidiosis. An unusual affliction in a patient in the seventh decade of life, at a site not reported previously with no past history of the same makes it imperative to ascertain the known facts about both the organism and the disease. However the histopathological report confirmed the diagnosis which reiterates the need to further study the pathogenesis of this condition.